The effect of feed supplemented with curcuma longa and moringa oleifera on IKTA quail growth performance and egg production - Pang, Liang Ee (2022)
Research using herbal ingredients to enhance animal feed efficiency has received increase attention as consumers preferred natural additives. This led to the aim of this study to determine the effect of feed supplemented with 4% of Curcuma longa powder and 0.3% of Moringa oleifera seed powder on quails’s growth performance and egg production. In this study, 42 Institut Kemahiran Ternakan Ayam (IKTA) female quails were randomly assigned to the control and a treatment group with three replications each. Proximate analyses were conducted to determine the nutritional content of the feed prior to feeding trials. The feed supplemented with C. longa powder and M. oleifera seed powder consists of 21.54% crude protein (CP) that meets the standard quail CP requirement. The weight gain, feed conversion ratio (FCR), egg production rate and egg yolk colour were determined in this study. The findings of this study showed that there was no significant difference (p the control and treatment groups for all the parameters studied. The average weight gain in treatment group (74.23 ± 11.28 g) was relatively higher compared to the control (72.24 ± 7.91 g). However, the average FCR for the control group (2.47 ± 0.36) was relatively lower compared to the treatment (2.61 ± 0.25). The average egg production rate from 6 weeks old to 9 weeks old between treatment group (63.49 ± 4.94%) and control (69.84 ± 1.62%) were not significantly different (p 0.05). The egg yolks from treatment group showed the average delta L*, a* and b* of -0.15, 0.03 and -0.12, respectively which indicates that the colour prone to darker shades of yellow. In conclusion, the findings of this study showed that the supplementation of 4% of C. longa powder and 0.3% of M. oleifera seed powder into the quail feed diet neither improves nor causes adverse effects on the growth performance and egg production of the quail.